Identification and physiological characteristics of potential indigenous bacteria as bioremediation agent in the wastewater of sugar factory - Pardamean, Mikchaell Alfanov; Islamy, R Adharyan; Hasan, Veryl; Endang Yuli Herawati,; Nurul Mutmainnah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Wastewater is the remainder of an activity released in the liquid form. Wastewater product is feared to have negative influence on the environmental balance; therefore, it is necessary to measure the quality standards of wastewater as a reference in the disposal and treatment. Bioremediation is an environmentally friendly technology utilizing microorganisms as agents in the process of cleaning or restoring wastewater conditions. The use of microorganism services can reduce the concentration of organic waste into simpler organic compounds by converting organic compounds into CO2, CH4, H2, and H2S, as well as water and energy intended for the process of growth and production of microorganisms in the remediation process. This study aims to identify the type of dominant bacteria growing in the wastewater of the sugar factory and has a potential role as a bioremediation agent for the waste. The method used in this study is the experimental, by observing several environmental parameters as indicators, among others, BOD, COD, TSS, and pH. The results of this study found two types of dominant bacteria, i.e., Staphylococcus aureus and Bacillus subtilis, then used as bioremediation agents. The bioremediation activity was able to reduce pH, BOD, and COD levels.